Lateral Lumbar Interbody Fusion in the Outpatient Setting with Multimodal Analgesic Protocol: Clinical Case Series - Jacob, Kevin C; Patel, Madhav R; Pawlowski, Hanna; Parsons, Alexander W; Vanjani, Nisheka N; Lynch, Conor P; Cha, Elliot DK; Prabhu, Michael C; Singh, Kern (Journal of minimally invasive spine surgery and technique, 2022)
Objective: Minimally invasive techniques and multimodal analgesia protocols have made spine surgery in the outpatient setting increasingly feasible. A number of spinal procedures have been documented in the outpatient setting, though the feasibility of lateral lumbar interbody fusion (LLIF) on an ambulatory basis has not been thoroughly assessed. To present a clinical case series of patients undergoing LLIF in the outpatient setting.Methods: A prospectively maintained surgical database was retrospectively reviewed to identify patients undergoing outpatient spine procedures with an enhanced multimodal analgesia protocol from October 2016 to February 2021. Patient demographics, medical and spinal diagnoses, procedural characteristics, operative duration, estimated blood loss (EBL), postoperative length of stay (LOS), postoperative pain scores, postoperative narcotic consumption, and incidence of any intra- or postoperative complications were collected. The state’s prescription monitoring program was queried to assess rates of filling narcotic prescriptions >6 weeks following surgery.Results: A total of 24 LLIF patients were included. Mean postoperative pain score was 5.8, and mean postoperative narcotic consumption was 26.8 oral morphine equivalents. All patients were discharged on the same day of surgery. No postoperative complications were observed. After the 6-week postoperative timepoint, 16.7% of patients filled a prescription for tramadol, 8.3% for hydrocodone, 4.2% for hydromorphone, 4.2% for cyclobenzaprine, and 4.2% for alprazolam. Conclusion: This clinical case series demonstrates that LLIF can be both safe and feasible in the outpatient setting, with minimal narcotic medication dependence in the postoperative period.